Identification of Acute Vaccine-Preventable Hepatitis in Individuals with Chronic Hepatitis in British Columbia between 1991 and 2007 - Lily Fang; Amanda Yu; Jane A. Buxton (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: In British Columbia (BC), hepatitis A virus (HAV) and hepatitis B virus (HBV) vaccines are provincially funded for persons with chronic hepatitis infections. PURPOSE: To assess the effectiveness of BC public health follow-up of HBV and hepatitis C virus (HCV) cases and immunization policy by determining the number of vaccine-preventable acute hepatitis infections reported following a chronic HBV or HCV diagnosis, by examining demographic characteristics and by observing temporal trends.